2016
DOI: 10.1080/14015439.2016.1207097
|View full text |Cite
|
Sign up to set email alerts
|

The influence of water resistance therapy on vocal fold vibration: a high-speed digital imaging study

Abstract: Results suggest that the depth of tube submersion appears to have an effect on phonation. Shallow immersion seems to promote smoother and more stable phonation, while deeper immersion may involve increased respiratory and glottal effort to compensate for the increased supraglottal resistance. This disparity, which is dependent upon the degree of flow resistance, should be considered when choosing treatment exercises for patients with various diagnoses, namely hyperfunctional or hypofunctional dysphonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 39 publications
6
26
1
5
Order By: Relevance
“…In addition, in the present study, the jitter parameter significantly decreased (P < 0.001), and this finding is consistent with studies conducted on semi-occluded vocal tract exercises (17)(18)(19). In particular, it is consistent with Guzman et al's study (2016), where they studied the impact of depth of immersion of tube in the water on perturbation measures and concluded that immersion to a depth of 5 cm reduces jitter (19).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In addition, in the present study, the jitter parameter significantly decreased (P < 0.001), and this finding is consistent with studies conducted on semi-occluded vocal tract exercises (17)(18)(19). In particular, it is consistent with Guzman et al's study (2016), where they studied the impact of depth of immersion of tube in the water on perturbation measures and concluded that immersion to a depth of 5 cm reduces jitter (19).…”
Section: Discussionsupporting
confidence: 82%
“…In particular, it is consistent with Guzman et al's study (2016), where they studied the impact of depth of immersion of tube in the water on perturbation measures and concluded that immersion to a depth of 5 cm reduces jitter (19). According to previous studies, after vocal fatigue, jitter increases (20)(21)(22), which may be associated with a reduction in sensory-motor control (23).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In a recent high-speed digital imaging study, CQEGG tended to increase during tube phonation into water compared to comfortable vowel production in normal-voiced subjects. Higher values were found at 10 and 18 cm of immersion compared to 5 cm [65]. …”
Section: Discussionmentioning
confidence: 99%
“…The latter are referred to as water resistance therapies (WRT) where LaxVox© and DoctorVox© are the commercially available products [10]. For WRT, the depth to which the tube is submerged under water defines the intraoral pressure and therefore influences the transglottic pressure difference [11]. Furthermore, the popping bubbles produced in the water cause a fluctuating intraoral pressure during phonation.…”
Section: Introductionmentioning
confidence: 99%